Libertinaje en el siglo XVII - Albiac, Gabriel (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2015)
This article tries to draw the polemical genealogy of the term and concept of “libertinism”. Its sense, as it is forged in early Modernity, in the works of Calvin, and in the backgroud of the first Protestant Reformation, is merely contemptuous and, above all, it is due to a clearly critical strategy: the construction of a fictional enemy in confrontation with which it is possible to reinforce the basis of modern Christianism.